Breast Self Examination (BSE) Training for Early Detection of Breast Cancer in Women of Childbearing Age - Kadir, Arisna; Dahniar, Dahniar; Yun Diniaty Rosidi, Indah (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Among all cancers, breast cancer (BC) is the highest cause of mortality in women. In 2012 there were 1.7 million cancer sufferers with 20% of breast cancer cases, this number is expected to fluctuate up to four times by 2020. Treatment of breast cancer will be more optimal if it is detected early, screening techniques that can reduce mortality can be carried out by everyone independently and effectively known as breast self-examination (BSE). The purpose of this service is to provide BSE training for early detection of breast cancer in fertile women (WUS) using community education methods that focus on women of childbearing age so they can carry out breast self-examination with training, lecture and question and answer approaches. This service was carried out in the work area of ​​BPM Hj. Rismawati Maros Regency which was attended by 16 participants. Evaluation of post-test results showed an increase in participants' understanding of breast cancer and BSE as a first step in breast cancer screening and readiness to do it routinely independently at home.